Frequência dos polimorfismos nos genes NLRP1, NLRP3, P2X7, IL1B e IL18 em pacientes com Leucemia Linfoblástica Aguda e sua influência no prognóstico clínico - Alves, Fabiola Silva (2020)
The dysregulation of the activation of the inflammasome complex by the presence of Single Nucleotide Polymorphisms (SNPs) is pointed out as one of the factors that promote neoplastic activity in the hematopoietic stem cell. Although the SNPs involving these complexes are associated with the manifestation of infectious and non-infectious diseases, the relationship with susceptibility or prognosis in leukemia patients in the Brazilian Amazon is still unknown. Thus, the aim of this study was to describe the frequency of polymorphisms in the NLRP1 (rs12150220 and rs35865013), NLRP3 (rs10750558 and rs10802502) genes, P2X7 (rs2230911 and rs3751143), IL1β (rs16944) and IL18 (rs187238) and its influence on clinical prognosis. A case-control study was carried out with 158 patients with ALL and 192 control individuals from a region of the Brazilian Amazon, the State of Amazonas. The genetic polymorphisms in the IL1β and IL18 genes were genotyped from the restriction fragment length polymerase- polymorphism chain reaction (PCR-RFLP). While the polymorphisms in the NLRP1, NLRP3 and P2X7 genes were genotyped using Real Time Quantitative PCR (qPCR). The IL1β C/T rs19644 genotype was associated with the risk of ALL development (C/C vs. C/T + T/T OR: 2.48 [95% CI: 1.26 - 4.88, p = 0.006]; CC vs C/T OR: 2.74 [95% CI: 1.37-5.51, p = 0.003]). The genotypes P2X7 A/C rs3751143 (OR: 2.30 [95% CI: 1.05-5.03, p= 0.036]) and NLRP3 G/G rs10754558 (OR: 7.44 [95% CI: 1.44 - 38.26, p = 0.016]) were associated with the risk of infectious comorbidities whereas, NLRP1 A/T rs12150220 (OR: 0.37 [95% CI: 0.16 - 0.87, p = 0.023]) was associated with protection against comorbidities. In addition, the association of the genotype NLRP1 A/G rs35865013 (OR: 2.72 [95% CI: 1.07 - 6.90, p = 0.034]) with the risk of relapse after treatment in ALL patients has been described. The variant IL1β rs16944 seems to predispose individuals from the Brazilian Amazon region to ALL. In addition, inflammasome SNPs are xi associated with the presence of infectious comorbidities and relapse episodes throughout treatment in individuals with acute lymphoblastic leukemia